Analisis Etika Bisnis Pada BMT Mitra Umat: Ketidakmampuan Membayar Tabungan Nasabah Sebagai Bentuk Pelanggaran Kepercayaan - Nursetiana, Herni; Azima, Najma; Zulfa, Amalina; Tsania, Afrida; Misidawati, Dwi Novaria; Islami, Putri Prasetya (Yayasan Cendekia Gagayunan Indonesia, 2025)
This research aims to analyse BMT Mitra Umat's inability to pay customers' savings as a form of violation of business ethics, especially the principles of honesty, responsibility, justice, and integrity in Islamic financial institutions. The research uses a qualitative descriptive method with a literature study approach, based on the analysis of Islamic business ethics theory and the concept of customer trust. The results showed that BMT Mitra Umat's inability to fulfil its savings payment obligations had a serious impact on the decline in customer trust and damage to the institution's reputation. This violation of the basic principles of business ethics worsens customer loyalty and potentially threatens the sustainability of the institution's operations. This research recommends the need for increased transparency, improved risk management, financial education to customers, and strengthened internal controls to restore public trust and ensure the sustainability of BMT as a trustworthy Islamic financial institution.